Multilayered Stub Loaded-SIR for Compact Dual-BPF and Quad-channel Diplexer Design - Ajeel, S. L.; Hammed, R. T. (Radioengineering society, 2024)
This paper considers a novel design technique of compact dual-BPF and four-channel diplexer for a multi-service communication system. The suggested dual-band passband filter is constructed by a double-layered stub loaded-stepped impedance resonator (SL-SIR), leading to a tiny circuit area, and lightweight, low cost, and good characteristic performance. Herein, the SL-SIR resonant odd-mode is used to realize the first passband, while the resonant even-mode is used to realize the second passband. Also, the proposed three-port quad-channel diplexer is performed by two different double-layered dual-passband filters, which also have a very compact circuit area. For practical verification, a two-passband filter working at 2.5/4 GHz with a circuit area of 91.7ă€–mmă€—^2 and a four-channel diplexer working at 2.5/4 GHz and 3.5/5.2 GHz with a circuit area of 0.0639 ă€–Î»_gă€—^2 excluding feeding ports are designed, manufactured, and measured. The electromagnetic simulated and measured responses are compared and discussed. Obviously, the comparison show good agreement improving the expected filtering response. The diplexer offers insertion/return losses of about (0.44/0.74) dB/(0.45/1.12) dB for channel 1/channel 2, and (21.30/21.72) dB/(19.81/20.54) dB for channel 3/channel 4.
Keywords: Stub loaded-stepped impedance resonator; double-layered dual-BPF; four-channel diplexer; compact multi-channel diplexer; multilayered dual-PBF